Chemical recycling and upcycling of poly(Bisphenol A carbonate) via metal acetate catalyzed glycolysis. (January 2023) - Nifant'ev, Ilya E.; Pyatakov, Dmitry A.; Tavtorkin, Alexander N.; Ivchenko, Pavel V.
Highlights: The study of Li, Na, K, Mg, Ca and Zn acetates in glycolysis of BPAC at 180 °C. Full conversion of BPAC after 1 h when using <0.01 wt% of Mg(OAc)2 or Zn(OAc)2 . The use of 1, 2-diols and α-alkyl-substituted 1, 3-diols leads to cyclic carbonates. DFT modeling of the metal acetate-catalyzed glycolysis of BPAC. Abstract: Prospective method of poly(bisphenol A carbonate) (BPAC) waste processing is based on catalytic glycolysis, combining recycling to bisphenol A (BPA) and upcycling with a formation of cyclic carbonates. With the aim of developing efficient solvent-free glycolysis of BPAC we studied catalytic behavior of Li, Na, K, Mg, Ca and Zn acetates in the reaction of BPAC with ethylene glycol (EG). With the use of EG as reagent and reaction media at 180 °С, down to 0.01 wt% of Mg(OAc)2 and Zn(OAc)2 catalyzed full conversion of BPAC to BPA and ethylene carbonate within 1 h. Acetates of alkali metals demonstrated lower activities and selectivities, Ca(OAc)2 was found to be almost inactive. DFT optimization of the metal complexes with components of the reaction mixture allowed to explain low catalytic activity of Li, Na, K and Ca acetates by relative stability of inactive metal phenolates, whereas Mg and Zn acetates tend to form active glycolate species and phenol. Theoretical investigations of the mechanism of Mg(OAc)2 and Zn(OAc)2 -catalyzed glycolysis of the model substrate diphenyl carbonate have determined the sequence of the reaction intermediates and transition states, thereby explaining the high catalytic activities of Mg and Zn acetates by relatively low values of the activation barriers amounted to ∼15 kcal/mol in G scale. Comparative experimental studies of 1, 2-, 1, 3-, 1, 4-diols and glycerol in glycolysis of BPAC have demonstrated high efficiency of Mg(OAc)2 and Zn(OAc)2 catalysts in the amount of less then 0.1 wt%, the yields of BPA exceeded 90%. Along with that, the high yields of cyclic carbonates were achieved when using 1, 2-diols and 1, 3-diols, containing alkyl substituents in α-position to –OH group.